2017
DOI: 10.3892/ol.2017.6801
|View full text |Cite
|
Sign up to set email alerts
|

APC downregulated 1 inhibits breast cancer cell invasion by inhibiting the canonical WNT signaling pathway

Abstract: Abstract. Canonical WNT signaling promotes breast cancer progression. Although APC downregulated 1 (APCDD1) may inhibit canonical WNT signaling, its role in breast cancer remains to be fully understood. The present study demonstrated that APCDD1 suppressed in vitro breast cancer growth and metastasis by inhibiting canonical WNT signaling. The present study demonstrated that APCDD1 expression was negatively associated with breast cancer cell invasion, which was consistent with previous studies that indicated th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 29 publications
(39 reference statements)
2
13
0
1
Order By: Relevance
“…The function and relative regulatory mechanisms of miR-663b in CRC tumorigenesis were additionally investigated, and the results demonstrated that ectopic miR-663b expression promoted cell proliferation, migration and invasion, and decreased apoptosis in vitro. It was demonstrated that dysregulation of APC serves important role in breast cancer cell invasion through WNT signaling pathway (31). The present study revealed that the overexpression of microRNA-663b promotes CRC cell invasion.…”
Section: Discussionsupporting
confidence: 56%
“…The function and relative regulatory mechanisms of miR-663b in CRC tumorigenesis were additionally investigated, and the results demonstrated that ectopic miR-663b expression promoted cell proliferation, migration and invasion, and decreased apoptosis in vitro. It was demonstrated that dysregulation of APC serves important role in breast cancer cell invasion through WNT signaling pathway (31). The present study revealed that the overexpression of microRNA-663b promotes CRC cell invasion.…”
Section: Discussionsupporting
confidence: 56%
“…When activated, this leads to a subsequent rise in β-catenin levels which precipitates its translocation into the nucleus to interact with transcription factors [T-cell factor (TCF) and lymphoid enhancer factor (LEF)] to promote cell proliferation and tumorigenesis (103). Both KOs also displayed reduced expression of APC down-regulated 1 (APCDD1), which also binds to WNT3a/LRP5 (102,104) and inhibits WNT/β-catenin LEF transcriptional signaling (105,106). The attenuation of negative WNT controls (APCDD1 and DKK4) in glycolytic KOs would, in theory, lead to a rise in β-catenin, which, if occurring in the cytoplasm, could interact with cadherin, bind to the actin filaments or TGF-β and alter cell-cell adhesion, thus resulting in a very loose mesenchymal phenotype contributing to metastasis.…”
Section: Reduction In Aldehyde Dehydrogenase Transcripts (Aldhs)mentioning
confidence: 99%
“…Aberrant regulation of Wnt/β-catenin signaling is observed in colon, ovarian, lung, prostate, liver, breast, and gastric cancers [12,[16][17][18][19][20][21]. Wnt/β-catenin signaling mediates the epithelial-tomesenchymal transition in gastric cancer [22], a process whereby epithelial cells are converted into migratory and invasive cells [23,24].…”
Section: Discussionmentioning
confidence: 99%